Colombia es pasión: um estudo sobre gestão e resultados de um projeto de construção de marca país - Herminio, Michele Canderolo (2013)
This work aims to: 1) describe the Colombian nation branding experience, entitled Colombia es Pasión based in the process steps: a) engagement; b) analysis; c) strategy; d) execution and audit and 2) assess the a) image impacts from an international perspective and b) the economic impact, in export, tourism and foreign direct investment areas. In order to do so, initially were presented concepts that support the understanding of the topic, as country brand, country brand identity, country image, place branding, destination brand and country of origin; following the case study, built from bibliographical, documentary and field research evidences, was presented. The case description and its interpretation in the light of process stages and phases can be found in Chapter 4. The impact assessment of the international image was conducted by content analysis of articles which contained the word Colombia in the title, in the newspapers The New York Times and El País, employing the software Atlas/TI. An index image was developed and its shows an improvement of 81.57% in the country image during the period that Colombia es Pasión was active, however, it was not possible to draw a causal link between the image improvement and the nation branding initiative. The economic impact of the program was evaluated by econometric models that considers the three target variables of the program: exports, tourism and foreign direct investment. The econometric analysis suggests that the program had positive economic impacts on exports and on the number of foreign tourists. The overall result of these two variables is, on average, equivalent to 1.28% of GDP in 2011. However, the most significant impact is on the dependent variables, taken as the program target. The effect of the program, on average, corresponds to 16.73% of exports and 13.63% of the number of foreign tourists in the year preceding the start of the program internationals actions, that is 2005.